The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fpls.2016.01632
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of MicroRNAs and Their Targets in the Leaves and Fruits of Eucommia ulmoides Using High-Throughput Sequencing

Abstract: MicroRNAs (miRNAs), a group of endogenous small non-coding RNAs, play important roles in plant growth, development, and stress response processes. Eucommia ulmoides Oliver (hardy rubber tree) is one of the few woody plants capable of producing trans-1, 4-polyisoprene (TPI), also known as Eu-rubber, which has been utilized as an industrial raw material and is extensively cultivated in China. However, the mechanism of TPI biosynthesis has not been identified in E. ulmoides. To characterize small RNAs and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 83 publications
8
23
1
Order By: Relevance
“…Analysis of conserved miRNAs revealed that miR159a_1, miR168a-5p, and miR166g-3p were highly expressed in all tissues. Among these miRNAs, miR159a_1showed the highest expression level in leaves, which was consistent with expression pattern of Eucommia ulmoides[ 17]. In rhizomes, expression levels of miR160, miR160e-5p, miR8175, miR319c_2, miR319b_1, miR319a_1, miR319a-3p, and miR319_1 were up-regulated and those of miR167d-5p, miR171b_2, miR397a_3, and miR160a-5p were significantly down-regulated compared with leaves and flowers.…”
supporting
confidence: 79%
“…Analysis of conserved miRNAs revealed that miR159a_1, miR168a-5p, and miR166g-3p were highly expressed in all tissues. Among these miRNAs, miR159a_1showed the highest expression level in leaves, which was consistent with expression pattern of Eucommia ulmoides[ 17]. In rhizomes, expression levels of miR160, miR160e-5p, miR8175, miR319c_2, miR319b_1, miR319a_1, miR319a-3p, and miR319_1 were up-regulated and those of miR167d-5p, miR171b_2, miR397a_3, and miR160a-5p were significantly down-regulated compared with leaves and flowers.…”
supporting
confidence: 79%
“…Two distinct pathways i.e., the MEP pathway and the MVA pathway play key roles in the synthesis of IPP which is the precursor of polyisoprene [ 6 , 39 ]. Pyruvate is a primary material in the MEP pathway [ 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a Tertiary relict species that has been a well-known medicinal plant in China for >2000 years [ 3 ]. Recently, the high productivity of gutta, i.e., trans -1,4-polyisoprene (TPI) in E. ulmoides has attracted broad attention [ 4 , 5 , 6 ]. E. ulmoides therefore has the potential to replace the commonly known para -rubber tree ( Hevea brasiliensis from the Euphorbiaceae, which only grows in tropical zones) because of its wide distribution in the subtropical and temperate ecozones and good resistance [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies have primarily focused on the underlying protein-coding genes involved in Eu-rubber biosynthesis (Suzuki et al 2012;Wuyun et al 2018), whereas little is known about the non-coding RNAs (ncRNAs) involved in this process (Wang et al 2016). Transcriptome analyses, based on deep sequencing, have revealed that more than 90% of the genome can be transcribed into ncRNAs (Kapranov et al 2007), which are classified as small ncRNAs (sncRNAs), or long ncRNAs (lncRNAs), based on length (Brosnan and Voinnet 2009).…”
Section: Introductionmentioning
confidence: 99%